Senescent human fibroblasts have increased FasL expression and impair the tumor immune response - Cruz-Barrera, Monica; Dulong, Joshua; Mansour Nehmo, Georgio; Sonn, Anthony; Moquin-Beaudry, Gaël; Benabdallah, Basma; Le, Oanh; Beauséjour, Christian (Frontiers in Immunology, 2025)
IntroductionSyngeneic mouse tumor models have shown that senescence influences the tumor immune response in multiple ways, including the induction of an immunosuppressive microenvironment or the promotion of immune cell recruitment. Yet, the impact of senescence on the tumor immune response in a humanized setting remains largely unexplored. MethodsTo address this question, we employed a combination cells co-culture models, tumor spheroids and mice bearing tumors immunogenic to human immune cells derived from the same donor. ResultsWe found that senescent fibroblasts exert a dual effect by enhancing the recruitment of immune cells into the tumor microenvironment while simultaneously promoting the apoptosis of T and NK cells. Mechanistically, we demonstrate that this apoptosis is primarily due to increased Fas ligand (FasL) expression on the surface of senescent fibroblasts. Increased FasL expression was observed on different human fibroblast cell lines in response to different senescence inducers with a particular robust effect in response to RAS-induced senescence. Deletion of FasL on fibroblasts was sufficient to prevent immune cell death and increase tumor cell killing in mice. DiscussionOur results identified the expression of FasL expression as a novel component of the senescent tumor microenvironment and highlight the importance of evaluating the impact of therapy-induced senescence in humanized models to understand and predict the outcome of cancer treatments.